The Implementation of Accrual-Based Accounting in Malaysian Public Sector: Opportunities and Challenges - Yusof, Nur Shawalliza; Jaafar, Hartini (International Business Education Journal, 2018)
Public sector reforms in Malaysia begun in the 1980s with the primary objective of improving the effectiveness, efficiency and transparency of governmental operational and financial management. The shift from cash-based accounting to accrual-based accounting in the public sector constitutes one of the measures outlined in the New Economic Model (NEM) under this reform initiative. The aim of this paper is to examine the opportunities and challenges faced by the Malaysian public sector in implementing accrual-based accounting. A review of previous literature in this area showed that accrual-based accounting improves decision-making processes, promotes better financial management and enhances public accountability. However, the transition process between these two accounting methods is not without challenges. Human resources competency, software and technology capability, accounting policies and standards suitability are identified as major challenges in the implementation effort. These challenges should be taken into consideration carefully by the government in order to ensure successful migration towards accrual-based accounting.